PERTUMBUHAN DAN HASIL TOMAT (Lycopersicon esculentum Mill) DATARAN RENDAH PADA KONDISI CEKAMAN KEKERINGAN - , VINNI DENIVITA TOME, Dr. Ir. Endang Sulistyaningsih, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Tomato (Lycopersicon esculentum Mill) is one of vegetables crops in Indonesia. Most of tomato variety planted in highlands areas. However there are some tomato varieties planted in lowlands areas (Purwati dan Khairunisa, 2002). Global warming in the world changing the effect rainfall distribution and induced low available soil water or drought. Drought inhibits plant metabolism and reduction of yield including tomatoes. The aim of the research were to determine effect of drought to the growth, yield and influence of some tomato varieties planted lowland areas mechanisms varieties tomato of lowland in drought. The research was conducted at the Tridharma research centre Faculty of Agriculture, Gadjah Mada University, Banguntapan, Yogyakarta and some Laboratory in Faculty of Agriculture, in October 2012 - February 2013. The research was arranged in split pot design with three blocks as replications. The main factors were watering intervals (1, 2, 4, and 8 days). The sub main factors were varieties of tomatoes (âZamrutâ, âPermataâ, Ratnaâ, âMirahâ, âTombatuâ, âTyranaâ, and âTymotiâ). Data were observed in morpholoicaly, physiological and yield of tomatoes. Conclusion were drought in general decreased soil water content, relative water content, total weight of fruits and total number of fruits. However, drought increased root shoot ratio at 48 day after planting (dap), specific leaf weight at 48 dap and net assimilation rate at 0-48 dap and proline content. The tolerance group had lower proline compared to that of the sensitive group.